Increasing Interest in Learning Indonesian Using the Smart Snakes and Ladders Learning Media in Class 1A Students - Adieza Putri, Nursyifa Fadilla; Rakhman, Patra Aghtiar; Rokmanah, Siti (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Classroom learning becomes a space for teacher actualization in applying creative learning media. The use of creative learning media is important for teachers in the teaching and learning process with students. Using varied strategies will reduce students' levels of boredom and will increase students' interest in learning. This research method is qualitative research in which researchers directly carry out observations and interviews in the field located in class 1A of SDN Sumampir. The research subjects themselves were students in class 1A. It is hoped that it will be able to arouse interest and stimulate learning activities in students, help the effectiveness of the learning process, attract and direct students' attention to concentrate on the content of the lesson, facilitate the achievement of goals to understand and remember the information provided, make learning more interesting, bring freshness and new variations. for students' learning experiences, especially in Indonesian language subjects. From the above, researchers have learning media that can be a solution and can be developed, namely